Human health exposure and risk assessment of environmental mercury contamination in residential areas of Camp 6, Tuba, Benguet - Diola, Ma.Brida Lea D. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
This research evaluates the potential exposure and health risk of mercury (Hg) contamination from diffferent exposure pathways on the residents of Camp 6 in Tuba, Benguet, using deterministic and probabilistic approaches. Hg in water of Bued River, drinking water and fish samples were found to be below detection limit while Hg in residential soils ranges from 0.1-1.5 mg/kg. Significantly higher concentrations in Bued river sediments (0.0131 to 2.1 mg/kg) were observed in areas near mining sites. Residents were surveyed to gather socio-economic, demographic, and site-specific exposure data for the risk assessment. A hazard index (HI) of 0.23 was computed from the deterministic assessment while the Monte Carlo simulations produced hazard indices of 0.46 and 0.91 at the 90th and 95th percentile, respectively. The results are less that 1 which indicates that the residents of Camp 6, at present, is not potentially at risk and they are not likely to have adverse health effects due to Hg exposure. In addition, the simulated daily Hg intake doses were verified using observed daily intakes derived from the measured Hg concentrations of the hair of 111 residents. Hair Hg concentrations from the participants range from 0.03 to 24.17 ppm with a geometric mean (GM) of 0.224 ppm. The simulated daily intake was found to be 2-3 times lower that the observed Hg data. Despite all the uncertainties and variability in the assessment, the Monte Carlo technique can be concluded to be a reliable approach in assessing humans' risk due to Hg exposure.
Thesis (M.S. in Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Environmental risk assessment -- Camp 6 -- Tuba -- Benguet; Health risk assessment -- Camp 6 -- Tuba -- Benguet; Mercury wastes -- Camp 6 -- Tuba -- Benguet